Role of the gut endoderm in relaying left-right patterning in mice. - Manuel Viotti; Lei Niu; Song-Hai Shi; Anna-Katerina Hadjantonakis (PLoS Biology, 2012)
Establishment of left-right (LR) asymmetry occurs after gastrulation commences and utilizes a conserved cascade of events. In the mouse, LR symmetry is broken at a midline structure, the node, and involves signal relay to the lateral plate, where it results in asymmetric organ morphogenesis. How information transmits from the node to the distantly situated lateral plate remains unclear. Noting that embryos lacking Sox17 exhibit defects in both gut endoderm formation and LR patterning, we investigated a potential connection between these two processes. We observed an endoderm-specific absence of the critical gap junction component, Connexin43 (Cx43), in Sox17 mutants. Iontophoretic dye injection experiments revealed planar gap junction coupling across the gut endoderm in wild-type but not Sox17 mutant embryos. They also revealed uncoupling of left and right sides of the gut endoderm in an isolated domain of gap junction intercellular communication at the midline, which in principle could function as a barrier to communication between the left and right sides of the embryo. The role for gap junction communication in LR patterning was confirmed by pharmacological inhibition, which molecularly recapitulated the mutant phenotype. Collectively, our data demonstrate that Cx43-mediated communication across gap junctions within the gut endoderm serves as a mechanism for information relay between node and lateral plate in a process that is critical for the establishment of LR asymmetry in mice.